2019
DOI: 10.1111/jvs.12739
|View full text |Cite
|
Sign up to set email alerts
|

Stature of dependent forbs is more related to the direct and indirect above‐ and below‐ground effects of a subalpine shrub than are foliage traits

Abstract: Question: Graminoid/shrubland communities include groups of forbs (herbaceous dicots) that differ in their traits, and in their direct and indirect responses to dominant neighbours. Although we have a growing knowledge of which traits might influence species' direct responses to dominant neighbours, and in particular the crucial importance of plant stature over foliage traits, less is known about the relationship between species' traits and direct responses to dominant neighbours.Location: An alpine graminoid/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
3
5
0
Order By: Relevance
“…Plant height appeared to be the best predictor of plant growth responses to A. ordosica , with the tallest species being facilitated by A. ordosica while the shortest species suffered competition from A. ordosica . These findings are consistent with those of previous studies, which show that competitive responses are more related to plant height than LDMC (Liancourt, Corcket, et al., 2005; Michalet, 2001; Michalet et al., 2008; Wang, Michalet, et al., 2019). Additionally, Liancourt, Callaway, et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Plant height appeared to be the best predictor of plant growth responses to A. ordosica , with the tallest species being facilitated by A. ordosica while the shortest species suffered competition from A. ordosica . These findings are consistent with those of previous studies, which show that competitive responses are more related to plant height than LDMC (Liancourt, Corcket, et al., 2005; Michalet, 2001; Michalet et al., 2008; Wang, Michalet, et al., 2019). Additionally, Liancourt, Callaway, et al.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, previous studies have also found that the responses of species to the dominant neighbours were largely determined by their functional traits or strategies, with stress‐tolerant species suffering competition and competitive species being facilitated (Graff & Aguiar, 2017; Liancourt et al., 2005). The contrasting responses of species to neighbours observed within a single community have been shown to be related to species functional traits, in particular plant height, a good proxy of species' competitive ability for light (Díaz et al., 2016; Grime, 1974; Liancourt et al., 2005, 2009; Michalet et al., 2008; Wang, Michalet, et al., 2019), rather than traits related to growth rate such as leaf dry mass content (LDMC; Ackerly, 2004; Kunstler et al., 2016; Wright et al., 2004). Thus, it has been found that in species‐rich communities, particularly those from intermediate environmental conditions and characterized by high functional divergence, there are functionally different species, or group of species, with contrasting responses to their neighbours, which could balance the community‐level responses (Michalet et al., 2015; Wang et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It should be the highest in the case of a collapse of facilitation or a shift back to a relatively high frequency of competition (Le Bagousse‐Pinguet, Xiao, et al., 2014; Maestre & Cortina, 2004; Michalet et al., 2006), both predicting a maximum of facilitation at these positions (Figure 1c,d), and because all complementarity processes are predicted to operate. The response of dependent species to dominant neighbours at intermediate environmental positions is highly variable and depends on their functional strategies (Bai et al., 2021; Michalet, Chen, et al., 2015; Wang et al., 2019), which is consistent with Choler et al. (2001), Liancourt, Callaway, et al.…”
Section: The Context Dependency Of Complementary Effects and Implications For Productivitymentioning
confidence: 56%
“…Overall, only indirect effects were observed for biomass in the fenced meadow, while there was no significant graminoid effect for either forb richness or composition in the two meadows. Wang et al (2019) also found weakly significant indirect facilitation due to competition release at the same site in the fenced meadow, while they did not assess interactions in the grazed meadow.…”
Section: Importance Of Indirect Facilitation Of Shrubs Against Grazers (Question 1)mentioning
confidence: 92%
“…Michalet et al (2015a) have shown in a similar ecosystem located in the sub-alpine belt that forb species had contrasting responses to both direct and indirect effects (due to the presence of graminoids) of D. fruticosa that ultimately influenced community composition. Additionally, Wang et al (2019) assessed, at the alpine belt and under ungrazed conditions, how the direct and indirect (due to the presence of graminoids) effects of D. fruticosa on forb species might be predicted from forb species trait values. However, none of these studies assessed how direct and indirect facilitation of D. fruticosa affects the productivity of forb communities through changes in taxonomic diversity and functional diversity.…”
Section: Introductionmentioning
confidence: 99%